USP5 Sustains the Proliferation of Glioblastoma Through Stabilization of CyclinD1 - Li, Gen; Yang, Tianquan; Chen, Yanling; Bao, Jianping; Wu, Di; Hu, Xiaohan; Feng, Chenxi; Xu, Lixiao; Li, Mei; Li, Gang; Jin, Meifang; Xu, Yunyun; et al. (Frontiers in Pharmacology, 2021)
Glioblastoma multiforme (GBM) is one of the most malignant primary tumors in humans. Despite standard therapeutic strategy with tumor resection combined with radiochemotherapy, the prognosis remains disappointed. Recently, deubiquitinating enzymes (DUBs) has been reported as potential cancer therapy targets due to their multifunctions involved in the regulation of tumorigenesis, cell cycle, apoptosis, and autophagy. In this study, we found that knockdown of ubiquitin specific protease (USP5), a family member of DUB, could significantly suppress GBM cell line U251 and DBTRG-05MG proliferation and colony formation by inducing cell cycle G1/S arrest, which was correlated with downregulation of CyclinD1 protein level. CyclinD1 had been reported to play a critical role in the tumorigenesis and development of GBM via regulating cell cycle transition. Overexpression of USP5 could significantly extend the half-life of CyclinD1, while knockdown of USP5 decreased the protein level of CyclinD1, which could be restored by proteasome inhibitor MG-132. Indeed, USP5 was found to directly interact with CyclinD1 and decrease its K48-linked polyubiquitination level. Furthermore, knockdown of USP5 in U251 cells remarkably inhibited tumor growth in vivo. Taken together, these findings demonstrate that USP5 plays a critical role in tumorigenesis and progression of GBM by stabilizing CyclinD1 protein. Targeting USP5 could be a potential therapeutic strategy for GBM.